The Analysis of Formative Assessment Needs in the Form of a Biology Comic Based on Problem-Based Learning to Train Critical Thinking Skills and Improve the Learning Outcome for Senior High School Students - Rucitra, Bidari Intan; Sari, Murni Sapta; Rahayu, Sofia Eri (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
The objective of this research is to comprehend the need for formative assessment in the form of Biology comics based on the PBL learning model. This comic intends to train critical thinking skills and improve students’ learning outcomes. A needs analysis was carried out by distributing questionnaires to senior high school students at MAN 2 Kota Malang, SMAN 5 Malang, and SMAN 7 Malang. Questionnaires were also distributed to students freely via social media. Moreover, interviews were also conducted with Biology teachers in MAN 2 Kota Malang. Another supporting data was the critical thinking skill test. The questionnaire results indicated that 70% of students needed these comics. Besides, Biology teachers also had a positive response to the variety of formative assessments in the form of Biology comics. The supporting data for the critical thinking test also showed the low category of 49.01 out of a maximum score of 100. Thus, it can be concluded that senior high school students need a variety of formative assessments in the form of Biology comics to train their critical thinking skills and improve their learning outcomes.